Changes in hospital referral patterns to skilled nursing facilities under the Hospital Readmissions Reduction Program - Kim, Kunhee Lucy (Med Care, 2019)
BACKGROUND: The Hospital Readmissions Reduction Program (HRRP) penalizes hospitals for higher-than-expected readmission rates. Almost 20% of Medicare fee-for-service (FFS) patients receive post-acute care in skilled nursing facilities (SNFs) after hospitalization. SNF patients have high readmission rates. OBJECTIVE: To investigate the association between changes in hospital referral patterns to SNFs and HRRP penalty pressure. DESIGN: We examined changes in the relationship between penalty pressure and outcomes before versus after HRRP Program announcement among 2,698 hospitals serving 6,936,393 Medicare FFS patients admitted for target conditions: acute myocardial infarction, heart failure, or pneumonia. Hospital-level penalty pressure was the expected penalty rate in the first year of the HRRP multiplied by Medicare discharge share. OUTCOMES: Informal integration measured by the percentage of referrals to hospitals’ most referred SNF; formal integration measured by SNF acquisition; readmission-based quality index of the SNFs to which a hospital referred discharged patients; referral rate to any SNF. RESULTS: Hospitals facing the median level of penalty pressure had modest differential increases of 0.3 percentage points (pp) in the proportion of referrals to the most referred SNF and a 0.006 standard deviation increase in the average quality index of SNFs referred to. There was no statistically significant differential increases in formal acquisition of SNFs or referral rate to SNF. CONCLUSION: HRRP did not prompt substantial changes in hospital referral patterns to SNFs, although readmissions for patients referred to SNF differentially decreased more than for other patients, warranting investigation of other mechanisms underlying readmissions reduction.